Neurofilament light chain is a cerebrospinal fluid biomarker in hereditary spastic paraplegia. Issue 5 (5th April 2021) - Kessler, Christoph; Serna‐Higuita, Lina M.; Rattay, Tim W.; Maetzler, Walter; Wurster, Isabel; Hayer, Stefanie; Wilke, Carlo; Hengel, Holger; Reichbauer, Jennifer; Armbruster, Marcel; Schöls, Ludger; Martus, Peter; et al.
Abstract: Objective: Despite the need for diagnostics and research, data on fluid biomarkers in hereditary spastic paraplegia (HSP) are scarce. We, therefore, explore Neurofilament light chain (NfL) levels in cerebrospinal fluid (CSF) of patients with hereditary spastic paraplegia and provide information on the influence of demographic factors. Methods: The study recruited 59 HSP cases (33 genetically confirmed) and 59 controls matched in age and sex. Neurofilament light chain levels were assessed by enzyme‐linked immunosorbent assay. The statistical analysis included the effects of age, sex, and genetic status (confirmed vs. not confirmed). Results: Levels of CSF NfL were significantly increased in patients with hereditary spastic paraplegia compared to controls (median 741 pg/mL vs. 387 pg/mL, p < 0.001). Age (1.4% annual increase) and male sex (81% increase) impacted CSF NfL levels in patients. The age‐dependent increase of CSF NfL levels was steeper in controls (2.6% annual increase). Thus, the CSF NfL ratio of patients and matched controls—expressing patients' fold increases in CSF NfL—declined considerably with age. Interpretation: CSF NfL is a reliable cross‐sectional biomarker in hereditary spastic paraplegia. Sex is a relevant factor to consider, as male patients have remarkably higher CSF NfL levels. While levels also increase with age, the gap between patients and controls is narrowing in older subjects. This indicates distinct temporal dynamics of CSF NfL in patients with hereditary spastic paraplegia, with a rise around phenotypic conversion and comparatively static levels afterward.